Rheumatic Fever in Large Cohort of Adolescents in Israel - Machluf, Yossy; Chaiter, Yoram; Farkash, Rivka; Sebbag, Anat; Fink, Daniel Lyon (Frontiers in Medicine, 2020)
Brief research report Abstract Background: Acute rheumatic fever (ARF) remains a major worldwide healthcare problem, despite its progressive decline in developed countries. The aims of our study were to estimate the prevalence of ARF among adolescents in Israel and to investigate risk factors. Methods: The study population consisted of 113,671 consecutive conscripts 16-19 years old, born during 1971-1993, who completed the medical profiling as part of the recruitment process to the IDF. ARF was diagnosed according to Jones criteria at time of illness, with confirmation relying on medical documentation and cardiologist evaluation including echocardiography. Results: The general prevalence rate of ARF was 0.12%. A downward trend was observed, from 0.19% among those born during 1971-1980 to 0.07% among those born during 1981-1993. Differences in prevalence of ARF were noted in sub-populations based on country of birth and origin - Israel, Ethiopia and the former soviet union (FUSSR). The prevalence rates of valvar disease among ARF+ and ARF- recruits were 15.7% and 0.95%, respectively. In multivariable logistic regression analyses, 4 variables were negatively associated with ARF: later birth year group, female gender, rural residence, youngest child; and 3 were positively associated with ARF: young parents, above normal BMI and valvar disease. Conclusion: Our study provides support for the documented decline in ARF prevalence and describes socio-demographic and anthropometric risk factors including the association with valvar disease and novel, risk factors including above normal BMI and young parents, both warranting further investigation which might help in developing societal level prevention strategies.